The effect of regime switching policy rules on economic growth - Norlin Khalid,; Nur Fakhzan Marwan, (Penerbit Universiti Kebangsaan Malaysia, 2013)
This paper empirically examines the relative effect of active and passive regime policy rules on economic growth. The time series data for a set of South-East Asian countries namely, Malaysia, Thailand and Singapore are used for the period 1971-2009. The Markov-switching (MSC) regression method is employed to characterize the regime switching for both monetary and fiscal policy reaction functions for each country. Then, the relative impact of these regime policies on long run output grow this estimated by using Auto Regressive Distributed Lag (ARDL) method. In order to control for different regime of policy rules, the dummy variables are included to capture the regime switching changes. The MSC regression shows that Thailand’s monetary policy is mostly active while fiscal policy is mostly passive throughout the sample covered. When both policies are considered, we note that Thailand changes its policy regimes very frequently. In contrast, Singapore’s regime switching is quite more stable. Singapore was in active monetary and passive fiscal for 20 years from 1971 to 1991. The country was in the passive monetary and passive fiscal regimes for 8 years before switching to passive monetary and active fiscal in year 2000 until 2009. Nevertheless, Malaysia’s monetary policy regimes are characterized as passive at all times while fiscal regime is active throughout the sample study. Furthermore, the ARDL cointegration shows that both monetary and fiscal policies are important in sustaining long run economic growth for Thailand. Meanwhile, Singapore’s economy is only positively determined by monetary policy while fiscal policy is insignificant. As for regime switching, our results indicate that only the monetary policy regime affects the economic growth in Thailand. This implies that an active monetary authority will only lead to a lower output growth. However, none of the regime variables is significant for Singapore which indicates that neither active nor passive regime really matters for economic growth.